IMPLEMENTASI KEBIJAKAN PROGRAM SI TETEH DALAM PELAYANAN PERIZINAN PADA DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN KARAWANG - Siti Sopiyah; Gili Argenti; Rudyk Nababan (Institut Pemerintahan Dalam Negeri, 2021)
The background of this research is that there is still physical printing of documents carried out at the Office of the Investment and One-Stop Service (DPMPTSP) Office of Karawang Regency. DPMPTSP is committed to providing the best service to the community, such as efforts to shorten the time, procedures, and costs for licensing and non-licensing, also supported by Electronic Services (PSE). This is regulated in Karawang Regent Regulation Number 40 of 2017 concerning Electronic Licensing Services and Karawang Regent Regulation Number 50 of 2018 concerning Amendments to Karawang Regent Regulation Number 40 of 2017 concerning Electronic Licensing Services. The purpose of this study is to describe how the implementation of the Si Teteh Program Policy in Licensing Services at the Office of Investment and One-Stop Integrated Services, Karawang Regency. This study uses a descriptive method with a qualitative approach. Then the data collection techniques were used in several ways, namely literature study, observation, interviews, and documentation. The data analysis technique was carried out through data reduction, data presentation, and also drawing conclusions and verification. The results of this study explain that the implementation of the Si Teteh program policy in licensing services has not been effective, because based on the theory of policy implementation by Charles O. Jones, (1994:166) which consists of three dimensions has not been fulfilled properly, among others: 1) Organization, Resources Human Resources consist of ASN and Non-ASN, facilities such as computers, printers and internet network; 2) Interpretation, socialization through social media, billboards, brochures, invitations from representatives of investment holders, mass media and online media as well; and 3) Implementation, an evaluation meeting is held every time there are problems or new regulations in the Si Teteh application.